An exploration of the mathematical learner identities of high school learners who participated in after school mathematics clubs in primary school - Hokonya, Wellington Munetsi (Rhodes University, Faculty of Education, Department of Education)
This study focuses on understanding mathematics learner identities of high school learners who participated in the South African Numeracy Chair Project after school mathematics clubs, an environment that afforded different mathematics identities from the traditional South African classroom. Mathematics learner identities feature prominently in current research on mathematics education because they affect whether and how learners engage in mathematics. They play a critical role in enhancing (or detracting from) learners' attitudes, dispositions, emotional development, and general sense of self as they learn mathematics. Development of positive learner mathematical identity is therefore useful in making learners commit to their mathematics work. South African primary mathematics education is described as being in a state of crisis, and various programmes are being implemented to develop intervention models to improve quality and ensure the effective teaching and learning of primary mathematics. The South African Numeracy Chair Project initiative at Rhodes University provides for longitudinal research and development programmes with primary mathematics teachers and learners from previously disadvantaged schools, in order to find ways of mitigating the crisis. The after school mathematics clubs provide extra-curricular activities focused on developing a supportive learning community where learners' active mathematical participation, engagement, enjoyment, and sense making are the focus. The clubs provide a supportive learning environment that is different to the traditional classroom and in which learners can participate actively and freely in mathematical activities. The study explores the nature of mathematics learner identities as learning trajectories that connect the past and future in negotiation of the present. It also seeks to discover how primary school club participation and experiences feature in the learners' mathematical identities. The study employs two theoretical frameworks to analyse qualitative data that was gathered in the form of spoken and written stories, by 14 learners who participated in the after school mathematics clubs in primary school. The stories covered learners' engagement in mathematics in different landscapes of practice that promoted the construction of different learner mathematical identities. A close analysis of the qualitative data revealed that learners' mathematical identities are heavily influenced by the values that were foregrounded in the after school mathematics clubs. The clubs valued hard work and encouraged learners to ask for assistance when in doubt. In line with the club ethos, the learners storied resilience and hard work in their narratives. In addition, although many learners storied Mathematics as difficult in high school, they chose to continue taking the subject.
Keywords: Mathematics-- Study and teaching (Secondary) -- South Africa; Mathematics-- Study and teaching (Elementary) Activity programs -- South Africa; Identity (Psychology) in children; After-school programs -- South Africa; School children Attitudes; Mathematics-- Study and teaching Psychological aspects -- South Africa; South African Numeracy Chair Project (SANCP)